Maybe you don't want to check all the details, but could look at a few equations here. Would you mind leaving a comment that you at least some part looks okay?- This way, I know that at least somebody checked it, too (although maybe not every step).

I want to reduce the PDE

$$ \sum_{i=1}^{n} \partial_i \left( \frac{\partial_i u(x)}{\sqrt{1+ \sum_{j=1}^{n} ( \partial_j u(x)^2 ) }} \right)=0$$

to an ODE by looking at solutions of the form $u(x):=f(||x||).$

We have $\partial_i u(x) = f'(||x||) \frac{x_i}{||x||}$ and $\partial_{i,j}u(x) = f''(||x||) \frac{x_i x_j}{||x||^2} + f'(||x||) \frac{\delta_{i,j}||x||^2 - x_j x_i }{||x||^3}.$

Applying the product rule to the PDE and multiplying by the square root in the demoninator, I get

$$ \left(\sum_{i=1}^{n} \partial_i^2 u(x) \right) \left(1+ \sum_{j=1}^{n} ( \partial_j u(x)^2) \right) - \left(\sum_{i,k=1}^n \partial_i u(x) \partial_k u(x) \partial_{i,k} u(x) \right) =0$$

Rewriting gives

$$\left(\sum_{i=1}^{n} \partial_i^2 u(x) \right) = f''(||x||)+f'(||x||) \frac{(n-1)}{||x||}$$

$$\left(1+ \sum_{j=1}^{n} ( \partial_j u(x)^2) \right) = 1+f'(||x||)^2$$

and finally

$$ \left(\sum_{i,k=1}^n \partial_i u(x) \partial_k u(x) \partial_{i,k} u(x) \right) = f'(||x||)^2 f''(||x||).$$

Is this all correct?


Yes. What you have computed all appear to be correct.

Just for sanity check you can simplify to

$$f'' + \frac{n-1}{\|x\|} [1 + (f')^2] f' = 0 $$

When $n = 2$ a solution should be $f = \cosh^{-1}(\|x\|)$. (This is because what you wrote down is the minimal surface equation and we know that one of them is given by the catenoid.) We know that for this $f$

$$ f' = \frac{1}{\sqrt{r^2 - 1}} $$


$$ f'' = -\frac{ r}{(r^2 - 1)^\frac32}$$

so you have confirmation that your formula works at least when $n = 2$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.